Analisis kebutuhan media flashcard berbasis augmented reality pada pembelajaran IPAS kelas V sekolah dasar - Sinar Tripamuji; Sita Isna Malyuna; Ina Agustin (Universitas Islam Nahdlatul Ulama Jepara, 2026)
This study aims to analyze the need for augmented reality-based flashcard media for teaching the human respiratory system in fifth-grade elementary school students. This study employed a descriptive qualitative approach supported by simple quantitative data obtained from a needs analysis questionnaire. The research was conducted at UPT SDN Kingking 2 Tuban, involving a fifth-grade teacher and nine fifth-grade students. Data were collected through observation, teacher interviews, questionnaires, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing, supported by source and technique triangulation. The findings showed that the learning process was still dominated by textbooks, student worksheets, teacher explanations, and simple instructional videos. Students experienced difficulties in identifying respiratory organs, understanding their functions, and relating the structure and function of the organs. The average daily test score was 66.2, with only three of nine students achieving the minimum learning criteria. The questionnaire results indicated that 88.89% of students needed more engaging and interactive learning media. Furthermore, 88.89% of students expressed interest in learning media featuring three-dimensional images and augmented reality. These findings indicate a strong need for visual, interactive, and concrete learning media to support students' understanding of the abstract concepts of the human respiratory system. Therefore, augmented reality-based flashcards are considered a relevant and potential learning medium to be developed for IPAS learning in fifth-grade elementary schools.